Diseminasi Inovasi Varietas Unggul Padi IPB 12 S melalui Metode Demplot untuk Peningkatan Produksi Padi di Desa Wingkomulyo - Eny Widajati; Muhammad Syukur; Ani Kurniawati; Setyo Pertiwi; Chusnul Arif; Silvan Timothy; Raihan Anwar Thaha (Institut Pertanian Bogor, 2026)
The Bogor Agricultural University community service program aims to disseminate the superior rice variety IPB 12 S in Wingkomulyo Village, Ngombol District, Purworejo Regency. Wingkomulyo Village had 33 hectares rice field, with a good irrigation system. The implementation method includes coordination of program implementation, rice planting demonstration plots, observation of growth, development, and plant production. Planting was carried out with a spacing of 30 cm x 30 cm, 14-day-old seedlings. The fertilizer dose per hectare spread was 150 kg of urea, 400 kg of NPK 15-10-12 and 95 kg of NPK 16-16-16 and 1 liter of silica fertilizer. Plant growth from the vegetative phase to the flowering phase was very good, but the plants fell before harvest due to heavy rain and strong winds. The production components observed included the average number of productive tillers (13.0), the number of grains per panicle (141.7), and grain production (6.0 tons GKP ha-1), are still below the yield potential of the IPB 12S variety as stated in the Variety Release Decree. This activity successfully introduced the IPB 12 S variety and IPB Prima cultivation technology to farmers in Wingkomulyo Village.